Positive solutions for a class of higher-order singular semipositone fractional differential systems with coupled integral boundary conditions and parameters - Wang, Y.; Liu, Lishan; Wu, Yong Hong (Springer Verlag, 2014)
In this paper, we study the existence of a class of higher-order singular semipositone fractional differential systems with coupled integral boundary conditions and parameters. By using the properties of the Green’s function and the Guo-Krasnosel’skii fixed point theorem, we obtain some existence results of positive solutions under some conditions concerning the nonlinear functions. The method of this paper is a unified method for establishing the existence of positive solutions for a large number of nonlinear differential equations with coupled boundary conditions. In the end, examples are given to demonstrate the validity of our main results.